Plant responses to simulated carbon capture and transport leakage: the effect of impurities in the CO2 gas stream - Lake, Janice A.; Lomax, Barry H. (Elsevier, 2018)
To deliver an effective transition from a carbon-based 24 to a carbon-free energy market, bridging technologies are required. One such possibility is the use of carbon capture and storage, (CCS). However, before such innovations can be rolled out a key requirement is to understand the environmental impact of these technologies. Recent experimental work has demonstrated that small scale CO2 leakage from CCS pipeline infrastructure has a localised and possibly transient impact. However, what remains unknown is the possibility of synergistic impact of impurities in the CO2 gas stream. Here we report the impact of two impurities SO2 (100 ppm SO2 in pure CO2) and H2S (80ppm H2S in pure CO2) on the growth and performance of two crop species (spring wheat, Triticum aestivum and beetroot, Beta vulgaris) in fully replicated experiments. Our data show that when compared to CO2-only gassed controls, the impact of these impurities are minimal as there are no statistically significant differences between performance parameters (photosynthesis, stomatal conductance and transpiration) or biomass. These results signify that from a plant health perspective it may not be necessary to completely remove these specific impurities prior to CO2 transportation.